Minimal contribution of P-gp on the low brain distribution of naldemedine, a peripherally acting μ-opioid receptor antagonist. Issue 2 (April 2019) - Watari, Ryosuke; Matsuda, Akihiro; Ohnishi, Shuichi; Hasegawa, Hiroshi
Abstract: Naldemedine tosylate, a peripherally acting μ-opioid receptor antagonist, is indicated for treatment of opioid induced constipation in both Japan and US. Naldemedine has limited ability to affect the central analgesic effect of opioid analgesics. In this study, we investigated the contribution of P-glycoprotein (P-gp) on the brain distribution of naldemedine. Naldemedine tosylate showed acceptable oral absorption in rats. Following a single oral administration of [ 14 C]-naldemedine tosylate to rats and ferrets, little radioactivity was detected in the region protected by the blood-brain barrier (BBB). In the assessment using Caco-2 cells, it was determined that naldemedine is a substrate for P-gp. The contribution of P-gp to the brain distribution of naldemedine was assessed using multidrug resistance 1a/b (mdr1a/b) knockout mice. While the brain-to-plasma concentration ratio (brain Kp) of naldemedine in the mdr1a/b knockout mice was 4-fold of that in the wild-type mice, the brain Kp in the mdr1a/b knockout mice was quite low (brain Kp < 0.1). These results suggest that the low brain distribution of naldemedine was due to the limited ability to cross the BBB rather than efflux by P-gp and therefore brain distribution of naldemedine would not be affected by concomitant administration of P-gp inhibitors or functional disorder of P-gp. Graphical abstract: Image 1